Maqasid-based good governance in theory and practice: the case of the Arab Spring in Egypt - Salim, Toha; Akhmetova, Elmira (2017)
This paper is an attempt to discuss the topic of good governance in Islam as a part of the main objectives of the Shari’ah by studying the case of the Arab Spring in Egypt. It addresses the historical and ideological roots behind various issues which led to the failure of the Islamists in Egypt in establishing good governance and to address the crises anchored in those thoughts that can help overcome challenges faced in the realm of good governance. As the paper establishes, Islamic sources provide the principles which can serve as the foundations of good governance in the contemporary world. Good governance means a set of institutions and policies that can effectively and successfully address the social, economic and political issues for the betterment of humanity. By analyzing the main trends in the contemporary Islamic political thought, i.e. traditionalists, salafists and reformists, the paper suggests that the weaknesses of these trends in understanding good governance and Maqasid-based political thought of Islam were the main reasons which contributed to the failure of the Arab Spring in Egypt. At the end, the paper suggests that Islamic jurisprudence and ethics should play an effective role in directing the contemporary Islamic political thought towards a model of good governance, while Maqasid al-Shari’ah is a necessary tool to widen the scope of the application of Islamic ethos in the contemporary context.